DID GOLD, BITCOIN AND FOREX AS SAFE HAVEN ASSET FOR SOUTH EAST ASIA INDEX DURING COVID 19 - Yen Sun; Vania Natasha; Edward Akil Tenggono (Bina Nusantara University, 2022)
The COVID-19 pandemic and the bearish market have led investors to find a safe-haven asset during this financial turbulence. Gold, US Dollar, and Bitcoin traditionally could be safe-haven assets in previous financial crises. However, safe-haven assets are mainly different during each market crash. Therefore, this paper aims to examine gold, US dollars, and Bitcoin as safe-haven assets during the COVID-19 market turmoil in several South East Asian countries such as Indonesia, Malaysia, Singapore, and the Philippines. All variables use daily data time series from January 2020 - September 2020. This study will conduct an empirical analysis using Generalized Autoregressive Conditional Heteroscedasticity (GARCH). Our result shows that during the COVID-19 pandemic, US Dollar could act as a safe-haven asset in Indonesia, Malaysia, and the Philippines. It implies that when the condition is uncertain during a pandemic, many investors switch their investments to US dollars in those three countries. On the other hand, gold and bitcoin are not safe-haven assets, but they could only act as hedging for several countries in South-East Asia.